Grynfelt-Lesshaft hernia a case report and review of the literature - Ploneda-Valencia, C.F.; Cordero-Estrada, E.; Castañeda-González, L.G.; Sainz-Escarrega, V.H.; Varela-Muñoz, O.; De la Cerda-Trujillo, L.F.; Bautista-López, C.A.; López-Lizarraga, C.R. (Annals of medicine and surgery, 2016)
Lumbar hernia account for less than 2% of al abdominal hernias, been the Grynfelt-Lesshaft's hernia (GLH) more frequent than the others. With approximately 300 cases published in the literature, the general surgeon may have the chance of treat it ones in their professional life. A 42-years old male with human immunodeficiency virus and Diabetes Mellitus presented to the outpatient clinic with a GLH. Preoperative classified as a type “A” lumbar hernia an open approach was scheduled. We performed a Sandwich technique with a sublay and onlay ULTRAPRO® mesh fixed with PDS® II suture without complications and discharged the patient 24-h after. After six months, the patient denied any complication. Primary (spontaneous) lumbar hernias represent 50–60% of all GLH. The preoperative classification of a lumbar hernia is mandatory to propose the best surgical approach. According to the classification of Moreno-Egea A et al., the best technique for our patient was an open approach. The Sandwich technique has demonstrated good outcomes in the management of the GLH. The surgical approach should be according to the classification proposed and to the experience of the surgeon. The Sandwich technique has good outcomes. •We present a Grynfelt-Lesshaft's hernia which account <2% of the abdominal hernias.•We document the new surgical approach for a Grynfelt-Lesshaft hernia.•We add a new case with a different technique with good outcomes.